History of agricultural research in India - Borthakur Anwesha; Singh Pradeep (Current Science, 2013)
India as a predominantly agicultural country attributes a major share of its overall developement to the agriculture sector. Indian agiculture is a miscellaneous and extensive sector involving a large number of stakeholders. India has one of the largest and institutionally most complex agricultural research system in the world. However, such complex research system was not a sudden developement. Instead, historically, it involved a process that started in the second half of the 19th century during the colonial period and eventually led to the establishment of the Imperial(now Indian) Council of Agricultural Research(ICAR). In the present research system, the role of ICAR at the national level in aiding, promoting and coordinating research and education activities across the country is of significant importance. In this article we trace the developement of agricultural research system in India, since the colonial era till today. Various factors influencing the overall developement of agricultural research system in the country are discussed. Although agriculture has been playing the most vital role in Indian economy, during the course of the study, it has been observed that not much emphasis has been given to the history of evolution of agricultural research in India.
Keywords: Colonial era; History of evolution; Indian agriculture; Research system